Informing radiography curriculum development: The views of UK radiology service managers concerning the 'fitness for purpose' of recent diagnostic radiography graduates. Issue 1 (September 2017) - Sloane, C.; Miller, P.K.
Abstract: Introduction: Recent years have seen significant changes in the way medical imaging services are delivered, rapid changes in technology and big increases in the number and ranges of examinations undertaken. Given these changes the study aimed to critically evaluate the fitness for purpose of newly qualified diagnostic radiography. Method: The study employed a grounded theory approach to analyse the interviews of 20 radiology managers from a range of medical imaging providers across the UK. Results: Four key themes emerged from the analysis. These were: curriculum content and structure review; diversification in the role of the radiographer; professionalism and coping and the reformation of career structures. Conclusion: The results indicate the role of the radiographer is now in a state of flux and challenge radiology managers and educators to design curricula and career structures which are better matched the role of the radiographer in the very rapidly changing technological, organisational and social contexts of modern society. Highlights: Imaging services have undergone many changes in recent years. The role of the radiographer is now in a state of flux. The role of the radiographer varies greatly between employers. There is a need to develop curricula and career structure's which match roles. Graduates must be excellent communicators, resilient and have realistic expectations.